Information System-Based Supply Chain Management Strategy to Improve Company Operational Performance - L. Happy Amira S (Jurnal Minfo Polgan, 2024)
Supply chain management is an integrated series of processes that encompass all steps from raw material procurement to the delivery of final products to consumers. The efficiency and effectiveness of the supply chain are crucial for the operational success of companies in achieving competitive advantage. This research aims to analyze an information system-based supply chain management strategy to enhance company operational performance. The methodology used in this study is a qualitative literature review with data collection from Google Scholar from 2001 to 2024. The results of the study indicate that the Information System-Based Supply Chain Management (ISBSCM) strategy has significant potential to improve company operational performance through the integration of information technology throughout the supply chain processes. By leveraging integrated information systems, companies can enhance efficiency, visibility, and responsiveness to market changes. However, the implementation of this strategy is not without challenges, including data security issues, costs, and change management.